Protection Conferred by Gallid Alphaherpesvirus 2 Vaccines Against Immunosuppression Induced by Very Virulent Plus (vv+) Marek’s Disease Virus Strains in Commercial Meat Type Chickens - Nagwa Khaled; Carissa Gaghan; Abdelhamid M. Fares; Christa Goodell; William Stanley; Raveendra R. Kulkarni; Isabel M. Gimeno (Pathogens)
Very virulent plus Marek’s disease virus (vv+MDV) induces severe immunosuppression in commercial chickens. In this study, we evaluated how three Gallid alphaherpesvirus 2 (GaHV-2) vaccines (CVI-988, rMd5-BAC∆Meq, and CVI-LTR) protected against two negative outcomes of vv+MDV infection: (1) reduced viability and frequency of immune cells in the spleen and (2) decreased efficacy of the CEO (chicken embryo origin) vaccine against infectious laryngotracheitis challenge. At 25 days post-infection with vv+MDV 686, all vaccines are protected against the reduced viability of splenocytes. However, there were differences in the frequency of splenic immunophenotypes among groups. Compared to the uninfected control, the frequency of B cells was reduced in the CVI-988/686 group but not in the rMd5-BAC∆Meq/686 and CVI-LTR/686 groups. T cell subset frequencies showed no difference between the negative controls and CVI-988/686; however, there was a reduction in activated CD4+ T cells in the rMd5-BAC∆Meq/686 group and in activated CD4+, activated CD8+, and γδ+ T cells in the CVI-LTR/686 group. We also demonstrated that the three vaccines protected against MDV-induced tumors, but only rMd5-BAC∆Meq and CVI-LTR protected against the negative impact of vv+MDV 648A strain on CEO vaccine efficacy. Our findings demonstrate important differences in the biology and/or mechanisms of protection of these vaccines.